STRATEGI PENGEMBANGAN PRODUK UNTUK MENINGKATKAN PENDAPATAN UMKM SUMBER WARAS DESA TAHUNAN KECAMATAN TEGALOMBO KABUPATEN PACITAN - Angga Adiaksa; Said Abadi (Investama : Jurnal Ekonomi dan Bisnis, 2022)
The product development strategy is an effort carried out by the company through the introduction of market opportunities, improvements in the technical aspects of production with innovation with the aim of increasing consumer or customer satisfaction. As is the case with the UMKM Sumber Waras in Tahunan Village, Tegalombo District, Pacitan Regency, whose products are superior in the Tahunan Village which are able to increase income, because UMKM Sumber Waras always develops their products continuously. The purpose of this study was to find out how the product development strategy was implemented in Sumber Waras UMKM, the product development modification strategy in Sumber Waras UMKM, and the impact of the development modification strategy on Sumber Waras UMKM. In preparing the thesis, the writer uses a qualitative descriptive research method, which is a problem-solving procedure by describing the situation based on the facts that appear as they are. Data collection techniques used are interviews and documentation.The results of this study can be concluded that the implementation of product development strategies carried out by UMKM Sumber Waras continues to strive to improve the quality of its products so that people's buying interest will increase. In the product development strategy based on the principles of Islamic economics, the Sumber Waras MSME still pays attention to several halal products, product quality, and product benefits. The strategy for modifying product development carried out by UMKM Sumber Waras is by maximizing promotions through social media, developing everything from packaging, product variants and product types. For this type of product, apart from making instant herbal medicine, Sumber Waras UMKM also makes other preparations, namely chips and processed milk. It aims to provide maximum value for consumers and win company competition by selecting innovative products. The impact after modifying product development is that the total income has increased compared to before. The main thing to increase revenue is from modifying product packaging, besides functioning to maintain product quality, product packaging can also provide information about products, and provide product security.